Maria Skłodowska Curie: l'obstination dans l'effort d'un génie - Dei, Luigi (Libere carte, 2017)
«Luigi Dei takes a very personal approach to presenting the life and achievements of Maria Skłodowska-Curie, setting them in the broader context of the history of science and European culture between the nineteenth and twentieth centuries. More specifically, he traces the links of the scientist, who twice won the Nobel Prize, with Poland (her homeland) and France (the country in which she lived, worked and made her outstanding scientific discoveries)» (Preface, Jan Piskurewicz).